An Investigation of the Efficacy of Various Policies Regarding Employee Welfare - Mohamad Harries J; P. Sudha; V. Pradeep (International Journal on Human-Computing Studies, 2023)
The project is centred on the establishment of charity centres. The title of the study was "a study on Employees welfare measures with special reference to Bescal Steel industry," and its topic was "a study on Employees welfare measures." The personnel of the business were the target audience for the research that was carried out. A systematic approach to the research topic is what is meant by the term "research methodology." An investigation into the degree of contentment felt by workers has been carried out through the use of research. A questionnaire was used to obtain the primary data that was needed. There were a total of 334 employees, but only 120 samples were included for this study. The secondary data was gathered through the use of the organization's website as well as its records. The data that was collected was interpreted using straightforward percentage tests. According to the statistics, the vast majority of employees are content with the provision of welfare facilities. However, in order to make improvements to the organization's welfare facilities for its workers, the researcher provides relevant recommendations to the company.